Development of graphical interface software for solar flare monitoring system - Mohamad Zulfahmi Mohamad Izham; Gan, Kok Beng; Mardina Abdullah; Siti Aminah Bahari; Sabirin Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Solar activity such as solar flares causes increased X-ray and ultraviolet ray flux. This event will cause sudden ionospheric disturbances (SID) and disrupts the communication systems as well as the space-based equipment on Earth. Public awareness especially to school students on the effects of solar activities towards humans on Earth is very important as the dependency of human daily life on space technology is increasing. The awareness has been conducted by the Space Science Center, Institute of Climate Change, UKM using UKM-SID™ system. Based on the program, it was found that school student experienced constraints in the process of analyzing data due to the absence of computers in schools. Therefore, UKM-SID™ system, with portable kit equipped with an interactive software to produce an easy-to-understand figure, was proposed. An algorithm was also developed to transfer the observed data onto the server in near real time. The developed Graphical Interface software showed a visualized sunrise and sunset patterns which is in agreement with the previous study. A solar flare was detected on 1 December 2020. The observed data is also successfully uploaded onto the server in near real time. Result shows that this new UKM-SID™ system is able to capture the solar flare occurrence. This new system is also at an optimal and sophisticated level compared to the technology that has been used. Hence, the researchers believe the UKM-SID™ is able to help educators, students and the general public in the learning of space science more effectively.